PENGARUH LIKUIDITAS DAN SOLVABILITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN SUBSEKTOR PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2020-2023 - Nadya Sakhira; Darma Wijaya; Fadli Ilyas (CV Edujavare Publishing, 2024)
Every business has its own way to achieve its profitability mission. Every company must compete as well as possible to achieve its goals, by working as hard as possible to achieve the company's goals. The way to find out how well a business can meet its current liabilities by using its current assets can be seen from its liquidity value. Financial ratios that play an important role for related parties in making choices in an organization also examine the capital structure of the business, namely the comparison between liabilities and equity as reflected in the debt to equity ratio (DER) which is the solvency ratio. The data collection method in compiling this thesis is a quantitative method, the researcher uses a statistical data processor (IBM SPSS Version 20). The results of the study show that Liquidity has a partial and significant negative effect on Profitability. Solvency has a partial and significant positive effect on Profitability. Simultaneously liquidity (Current Asset) and solvency (debt to equity ratio) have a positive effect on Profitability.